UPAYA GURU DALAM MENGATASI PERILAKU KENAKALAN SISWA DI SMPN 11 MANDAU - Diana Sari; Charlina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to describe several aspects related to student delinquency at SMPN 11 Mandau, which includes: 1) Forms of student delinquency, 2) Causes of such delinquency, 3) Obstacles faced by teachers in addressing these behaviors, and 4) Efforts made by teachers to manage delinquent behavior. This study employs a qualitative approach with a case study design, involving informants such as the school principal, the eighth-grade homeroom teacher, and eighth-grade students. Data were collected through interviews, observations, and documentation. The findings reveal that: 1) The forms of student delinquency include actions such as hiding classmates' belongings, fighting, being disruptive, playing during lessons, skipping school without explanation, being difficult to manage, asking friends for money, smoking, violating school uniform rules, arriving late to school, lying, teasing classmates, calling friends by their parents' names, and posting inappropriate content on social media. 2) The causes of student delinquency stem from both internal (endogenous) and external (exogenous) factors. 3) The obstacles teachers encounter in managing delinquent behavior include a lack of support and attention from parents regarding their children's behavior. 4) Teachers' efforts to address delinquency involve preventive actions like giving advice during class; corrective measures such as monitoring student behavior and communicating with parents; and developmental strategies like advising students involved in delinquent acts.